Use of Work Sampling to Determine Standard Time in Sales Outlet Performance: A Case Study - Rosyidi, Moh Ririn; Izzah, Nailul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Working time measurement is an attempt to identify the typical time required to finish a job in order to achieve a balance between output produced and labour performed. During the investigation, the problem was that employee working hours varied, thus it was required to enhance the working hours of sales outlet personnel. The findings of observations in non-productive areas were 0.27, indicating that there was still allowance time occurring at that site, indicating that research must be conducted continually. Trying to achieve standard time throughout sales outlet working hours and looking for strategies to boost outlet worker efficiency during the job process. The work sample approach was employed in the company's research, and the results showed that the standard time for a sales outlet to serve each customer required a minimum of p.1= 6.162 minutes, p.2= 8.453 minutes, for a total of 18.17 minutes. The standard productivity that two outlet employees must achieve during one shift (6 working hours) can be calculated using the standard time computation, which is a minimum of 19.81 ≈ 20 pcs of products sold.